The Effect of Organizational Justice on Organizational Commitment: A Case Study At PT. Bakrie Sumatera Plantations Tbk - Aprilia Handayani; Aiyub Aiyub; Faisal Matriadi; Yusniar Yusniar (Management Research and Behavior Journal, 2022)
This study was conducted to examine the effect dimensions of Organizational Justice (distributive justice, procedural justice, and interactional justice) on Organizational Commitment to employees of PT. Bakrie Sumatera Plantations Tbk. The population in this study were all head office employees of PT. Bakrie Sumatera Plantations Tbk by saturated sample of 102 people. primary Data collected by questionnaire, The analysis method used is multiple linear analysis technique using SPPS 26. The results of this study found that distributive justice And interactional justice have a positive and significant on organizational commitment. while Procedural justice has no effect on organizational commitment.  Based on the coefficient analysis determination, the R value is 0.788, which shows that the relationship between all dimensions of organizational justice and organizational commitment is quite strong. The R Square value is 0.620 which indicates that 62% of the organizational commitment variable can be explained by organizational justice.